Greening Sport for Development and Peace: A Socio-Ecological Approach - Giulianotti, Richard (Frontiers in Sports and Active Living, 2021)
The global ‘sport for development and peace’ (SDP) sector uses sport as a field of social activity to promote diverse types of non-sport social development. In this short perspective paper, I critically examine and advocate the engagement of SDP with environmental issues. I argue for the adoption of a ‘socio-ecological’ approach, to enable a greening of SDP that promotes both environmental and social justice. To that end, the paper is organized into four main parts. First, I situate the discussion with respect to key literature on SDP and the environment. I then outline some of the main contextual factors that need to be considered on sport, development, and the environment. Third, I set out several core principles that should underpin the socio-ecological greening of SDP. Fourth, I examine how these principles may be implemented within SDP.